Representation of Filipiniana LGBT books in selected university libraries in Metro Manila - Inciong, Juan Bernabe C. (2014)
The Lesbian, Gay, Bisexual, and Transexual (LGBT) community has always been a sector of society that is constantly under scrutiny. Because of this, LGBT literature has always been an outlet for them to discuss their issues. In this light, the study focused on the representation of LGBT in the library, in particular, the Filipiniana section. Three university libraries in Metro Manila were chosen, name hidden under guidance of the faculty for ideological reasons.